2016
DOI: 10.1186/s41256-016-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

An instrument based on protection motivation theory to predict Chinese adolescents’ intention to engage in protective behaviors against schistosomiasis

Abstract: BackgroundFurther advancement in schistosomiasis prevention requires new tools to assess protective motivation, and promote innovative intervention program. This study aimed to develop and evaluate an instrument developed based on the Protection Motivation Theory (PMT) to predict protective behavior intention against schistosomiasis among adolescents in China.MethodsWe developed the Schistosomiasis PMT Scale based on two appraisal pathways of protective motivation- threat appraisal pathway and coping appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…Studies on PMT have indicated that its constructs have high importance in predicting cancer-preventing behaviors [11][12][13]. Due to challenges in motivating women to participate in cervical cancer screening, Bai et al in china studied the role of PMT in predicting their tendency toward performing cervical cancer screening [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on PMT have indicated that its constructs have high importance in predicting cancer-preventing behaviors [11][12][13]. Due to challenges in motivating women to participate in cervical cancer screening, Bai et al in china studied the role of PMT in predicting their tendency toward performing cervical cancer screening [14].…”
Section: Introductionmentioning
confidence: 99%
“…These two assessments are taken by individuals to do something intentionally with different degrees of protection or risk which is called protection motivation (21). So far, PMT has been used in different areas of study such as breast cancer (20), wireless security at home (22), preventive behaviors from infectious diseases in poultry keepers (23), skin cancer in farmers (24,25), drought (26), schistosomiasis (27), reductive behaviors of flood (28), risk of fire in deserts (29), etc. With respect to the mentioned ideas and by paying attention to the importance of PMT in the investigation of workers' protective capacity and perception, as well as the fact that up to this time (to the best of our knowledge), no study has been conducted to examine PMT in greenhouse workers, and also since Jiroft is an important region for agricultural products cultivation, especially greenhouse products, therefore, the current study was conducted to examine predictors of safety behavior in workers of Jiroft greenhouses based on PMT in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The studies performed on PMT indicate that its constructs have a high importance in predicting cancer preventing behaviors (11)(12)(13). Due to challenges in motivating women to participate in cervical cancer screening, Yang et al in china studied the role of PMT on predicting tendency toward performing cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%